Apparatus for controlling the position of an operating device in the transversal plane of a chain trench excavator - M. E. Agapov (Вестник СибАДИ, 2017)
The present article contains results of theoretical researches of apparatus for controlling an operating device in the transversal plane of a chain trench excavator. The author describes an apparatus for controlling an operating device in the transversal plane of a chain trench excavator. There is described the work of control apparatus at occurrence of perturbation actions. There are revealed dependences of influencing key parametres of control apparatus on verticality of open trench’s walls and productivity of an excavator expressed in a trench’s length.